Peningkatan Kompetensi Videografi Drone bagi Siswa Jurusan Kehutanan SMK Negeri 1 Tualang, Siak - Ikhsani, Hanifah; Sabri, Erwanda Trio Bintan; Nugraha, Lefdi Agung; Agustina, Dinda Tri; Putra, Agung Kartika; Allasselcida, Anesha; Maryani, Maryani; Mohta, Gandhiko (Universitas Negeri Gorontalo, 2026)
This community service activity aimed to enhance the competencies of Forestry students at SMK Negeri 1 Tualang, Siak Regency, in drone-based videography using Unmanned Aerial Vehicle (UAV) technology. The training was conducted through an experiential learning approach that integrated theoretical instruction, technical demonstrations, and hands-on field practice. Training materials covered UAV fundamentals, flight safety, and aerial videography techniques relevant to forestry applications. The effectiveness of the program was evaluated using pre-test and post-test methods, supported by observations and interviews. The results indicated a substantial increase in the participants’ average scores, from 57.91% before the training to 96.51% after the training. The Wilcoxon Signed Rank Test revealed a statistically significant difference between pre-test and post-test results (p 0.05), confirming the positive impact of the training on students’ knowledge and technical skills. In addition, the program fostered improved confidence, discipline, and responsibility in drone operation. This activity contributes to strengthening vocational competencies and technological literacy in forestry education.